Mycosynthesis, Characterization of Zinc Oxide Nanoparticles, and Its Assessment in Various Biological Activities - Asif Kamal; Malka Saba; Khetab Ullah; Saeedah Musaed Almutairi; Bandar M. AlMunqedhi; Mohamed Ragab abdelGawwad (Crystals, 2023)
In recent years, nanotechnology has become one of the emerging fields of nanoparticle synthesis using biological processes. The use of mushroom extract is one of the most important methods for biological synthesis due to the presence of abundant biologically active compounds. In this study, Zinc Oxide nanoparticles (ZnO NPs) were synthesized using Daedalea sp. mushroom extract. The nanoparticles had an average size of 14.58 nm and irregular morphology, which shows its prominent character. Various analytical techniques including FTIR, X-ray diffraction, EDX, and UV-Vis spectrum showed a broad absorption between 350 and 380 nm, which indicates the synthesis of ZnO NPs. The characterized NPs were exploited for a wide range of biomedical applications including biocompatibility, antifungal, antileishmanial, and antibacterial studies. The ZnO nanoparticles showed a strong antibacterial effect against gram-positive (Klesbsilla pneumonia and Staphylococcus aureus) and gram-negative (Eschericia coli and Pseudomonas aeruginosa) bacteria. Furthermore, the ZnO nanoparticles also showed a high antifungal effect against Aspergillus niger fungus.